A survey of clinical laboratory instrument verification in the UK and New Zealand. (March 2019) - Hand, Matthew; Crampton, Andrea; Thomas, Annette; Kilpatrick, Eric S
Background: Clinical laboratory instrument verification testing is often an accreditation requirement. However, it is not known what verification procedures are in routine use or how often the process identifies problems which need addressing prior to testing clinical samples. Objective: To investigate which standards are currently being used for laboratory verification in UK and New Zealand (NZ) clinical laboratories and to help establish if the activity justifies the effort required. Methods: A survey of verification of clinical laboratory instrumentation was distributed to members of the Association for Clinical Biochemistry and Laboratory Medicine and New Zealand Institute of Medical Laboratory Scientists. The survey consisted of questions on the verification elements used and whether acceptance criteria were met. Results: Nineteen of 72 (26%) of responders only used organization-developed protocols for verification, 20/72 (28%) solely used national/international guidelines, while 16/72 (22%) used a combination. Manufacturers' claims were partly or entirely used as acceptance criteria for imprecision (89%), accuracy (64%) and analytical measuring range (94%), with these being met on 61%, 67% and 93% of occasions, respectively. For patient comparison and linearity, acceptance criteria were met by 71% and 91%. Only 27–36% undertook any troubleshooting before accepting a failed component of verification. Conclusions: Laboratories in the UK and NZ are currently using a variety of verification standards and acceptance criteria for instrument verification. It is common for instruments to fail, especially following the assessment of imprecision and accuracy. While this suggests the process is warranted, only a minority address failed elements before accepting verification.